Association of restless legs syndrome and obesity: A sub-population of the MASHAD cohort study - Azam Vafaei; Fatemeh Khorashadizadeh; Maryam Saberi-Karimian; Sara Saffar Soflaei; Mahnaz Amini; Abolfazl Rashid; Sara Yousefian; Gordon A. Ferns; Habibollah Esmaily; Majid Ghayour-Mobarhan; Reza Salaran; Fatemeh Taherian (Neurobiology of Sleep and Circadian Rhythms)
Introduction: Restless Legs Syndrome (RLS), as a relatively unknown sleep disorder, often associated with obesity. The purpose of this study was to examine the relationship between RLS and different definitions of obesity within the Mashhad stroke and heart atherosclerotic disorder (MASHAD) cohort study population. Methods: A total of 1006 subjects, with an average age of 57 (51.75–63.00) years old, were randomly selected from the MASHAD cohort study phase II. This sample included 449 males and 557 females, who were contacted by phone to inquire about RLS. Anthropometric measurements such as weight, height, waist circumference (WC), and hip circumference (HC) were taken. Central obesity was defined as a WC > 90 cm for men and >85 cm for women, as well as a waist-to-hip ratio (WHR) greater than 0.90 for men and 0.85 for women. Statistical analyses were conducted using R version 4.3.2 for Windows, with a significance level set at a two-sided P-value<0.05. Chi-squared and Fisher's exact tests were used to compare the categorical variables between two study groups. Logistic models applied to evaluate the association between RLS and BMI while adjusting for age effects. Results: The study found a significant relationship between RLS and employment status (p-value = 0.04), marital status (p-value = 0.05), and BMI (p-value<0.001). The results showed that in the total population, the OR of RLS in subjects having BMI>30 kg/m2 increased to 1.50(1.10–2.03) after adjusting for confounding factors (p-value<0.01). A BMI>30 kg/m2 increased odds of RLS by 1.72 times in males (95%CI: 1.03–2.84, p-value<0.05), however this association was diminished after adjustment (OR = 1.20, 95%CI: 0.64–2.17). There was no significant association between BMI and RLS in females. Moreover, there was no significant association between RLS and obesity based on WC and WHR in fully adjusted model respectively. Conclusion: There was a significant association between BMI and RLS. A BMI>30 kg/m2 increased the odds of RLS by 1.50 times in the study population.